1992
DOI: 10.1107/s0021889892004801
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure determination of lithium diborate hydrate, LiB2O3(OH).H2O, from X-ray powder diffraction data collected with a curved position-sensitive detector

Abstract: The crystal structure of lithium diborate hydrate, LiB2O3(OH).H2O, has been solved ab initio and refined by the Rietveld method from powder diffraction data collected with a curved position‐sensitive detector (INEL CPS120) using Debye–Scherrer diffraction geometry with monochromatic X‐rays. In the first stage the indexing of the powder pattern was performed by the successive dichotomy method from data collected with a diffractometer using Bragg–Brentano geometry. The lattice parameters are a = 9.7984 (10), b =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The very first SDPD realized by using FULLPROF was made in this team in 1992. Citing only a few of the first SDPDs using WPPD methods and made in the range 1988–1994, one can find nine publications in the Louër’s group (Louër et al , 1992; Petit et al , 1993, 1994; Pivan et al , 1994; Pelloquin et al , 1994; Guillou et al , 1994; Gascoigne et al , 1994; Bénard et al , 1994a, b), this is a quite large contribution since, in these times, the number of SDPDs per year was small (Figure 2). These applications certainly contributed to making it more widely known that a difficult step (WPPD) was now realized more easily by using a well-distributed Rietveld computer program ( FULLPROF ).…”
Section: More Wppd Applicationsmentioning
confidence: 99%
“…The very first SDPD realized by using FULLPROF was made in this team in 1992. Citing only a few of the first SDPDs using WPPD methods and made in the range 1988–1994, one can find nine publications in the Louër’s group (Louër et al , 1992; Petit et al , 1993, 1994; Pivan et al , 1994; Pelloquin et al , 1994; Guillou et al , 1994; Gascoigne et al , 1994; Bénard et al , 1994a, b), this is a quite large contribution since, in these times, the number of SDPDs per year was small (Figure 2). These applications certainly contributed to making it more widely known that a difficult step (WPPD) was now realized more easily by using a well-distributed Rietveld computer program ( FULLPROF ).…”
Section: More Wppd Applicationsmentioning
confidence: 99%
“…After these early results, solutions of a variety of new structures have been reported for data collected with different instrumental configurations and sources of radiation, e.g. ZrNaH(PO 4 ) with a conventional diffractometer and CuKα 1,2 radiation (Rudolf and Clearfield 1985), Nd(OH) 2 NO 3 .H 2 O with a diffractometer using monochromatic CuKα 1 radiation (Louër and Louër 1987), α-CrPO 4 with synchrotron X-rays (Attfield, Sleight and Cheetham 1986), FeAsO 4 from TOF neutron data (Cheetham et al 1986), Al 2 Y 4 O 9 and I 2 O 4 from combined synchrotron X-ray and neutron diffraction data (Lehman et al 1987), LiB 2 O 3 (OH).H 2 O from data collected by means of a curved position sensitive detector, Debye-Scherrer geometry and CuKα 1 radiation (Louër, Louër and Touboul 1992). A partial compilation of the earlier structures to be solved from first principles from powder data has been made by Cheetham (1995).…”
Section: Historical Overviewmentioning
confidence: 99%
“…It is worth noting that strictly speaking photographic films are indeed position sensitive detector, nevertheless the name PSD is usually used for directly readable gas filled or solid state detectors. The introduction of such devices has induced large developments of DSH diffractometers (Shishiguchi et al , 1986; Plévert et al , 1989; Louër et al , 1992; Louër et al , 1995; Deniard et al , 1991; Jouanneaux et al , 1992; Evain et al , 1993; Stahl and Thomasson, 1992; Stahl, 1993; Stahl and Hanson, 1994; Christensen et al , 1995; Christensen et al , 1996) and more recently of SB setups (Stahl, 2000). Moreover, new diffractometers using bidimensional PSD which directly record the whole Debye rings are also developed, first at the synchrotron sources (Gualtieri et al , 1996; Norby, 1997) and more recently in laboratories (He and Preckwinkel, 2002).…”
Section: Description and Recent Developments Of Conventional Diffractmentioning
confidence: 99%
“…The important point is that using a convenient calibration method, the detector response can be perfectly corrected. In the beginning of the 1990s several authors and in particular the group of Louër have shown that such a diffractometer is very well suited for structural analysis through the Rietveld method (Louër et al , 1992, 1995).…”
Section: Description and Recent Developments Of Conventional Diffractmentioning
confidence: 99%